A 1000‐Year Record of Temperature From Isotopic Analysis of the Deep Critical Zone in Central China. Issue 5 (10th March 2023) - Wang, Hongxiu; Li, Han; Xiang, Wei; Lu, Yanwei; Wang, Huanhuan; Hu, Wei; Si, Bingcheng; Jasechko, Scott; McDonnell, Jeffrey J.
Abstract: Temperature proxies for paleoclimate reconstruction have been made typically via ice cores, tree rings, stalagmites, and lake sediments. While extremely useful, these proxies can be limited spatially. Here we sampled a 98 m "soil core" from Loess Plateau of China and examined the relationship between pore water isotopic values and hydroclimate history. We extracted soil pore water for δ 18 O, δ 2 H, and 3 H and measured chloride concentration. The 3 H‐peak at 6 m and chloride mass balance were used to turn depth into calendar year. A 1000 year span was revealed. δ 18 O and δ 2 H values between 14–50 m were anomalously low—bracketing well the Little Ice Age period from 1420 to 1870. The identification was consistent with other standard proxies in the region and showed the same temporal dynamics of temperature anomalies. Our study shows the potential of stable isotopes of soil water for paleoclimate reconstruction in deep soils. Plain Language Summary: While paleoclimate reconstructions have been made with ice cores, tree rings, lake sediments and other proxies, few if any studies have explored the potential use of soil cores from the unsaturated zone to tease out paleoclimate information. Here, we report the soil water stable isotope data for an unusually deep, unsaturated zone soil core from the Loess Plateau of China. We found that waters extracted from the soil have relatively low δ 2 H and δ 18 O values in between the depths of 14–50 m. Waters at these depths likely derive from precipitation from the Little Ice Age period that occurred in that region of China from 1420 to 1870. Beyond simple time period identification, our isotope signal also captured the temperature dynamics during the Little Ice Age. We determined this by analyzing pore waters at 20 cm intervals. Tritium ( 3 H, a radioactive tracer) and a salt mass balance method enabled us to covert core depth increments into calendar year. Our study shows the potential of soil water extractions from the deep critical zone for meaningful interpretation of paleoclimate conditions. Key Points: A 98 m "soil core" from the Loess Plateau of China recorded clear paleoclimate information δ 2 H and δ 18 O values of extracted soil water between 14 and 50 m were anomalously low relative to the rest of the core The 14–50 m soil pore water bracketed the Little Ice Age period from the years 1420 to 1870